Complete mitochondrial genome of near threatened fish species Osteobrama belangeri (Cypriniformes: Cyprinidae) - Anindya Sundar Barman; Mamta Singh; Pramod Kumar Pandey (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genome of Osteobrama belangeri was obtained, using Illumina high-throughput NextSeq 500 with 2 × 150 bp sequencing of mitochondrial DNA. The mitochondrial genome of O. belangeri was 16,602 bp in length (GenBank Accession No. KY887473), comprised of 13 protein coding genes, 22 tRNA genes, 2 rRNA genes and a control region, i.e. D-loop. In present mitogenome, 11 short sequence repeats were identified and validated in silico. The arrangement of genes was found identical to other Cypriniformes fish mitogenomes, available in NCBI database. Phylogenetic relationship established in the present study also supported that genus Osteobrama is member of subfamily Cyprininae (tribe: smiliogastrini) not Cultrinae, which provide useful insights into taxonomic status of the genus.